Foods, nutrient intakes and Mediterranean dietary pattern in midlife are not associated with reaction times: a longitudinal analysis of the UK Women's Cohort Study. Issue 2 (28th January 2021) - Zhang, Huifeng; Hardie, Laura; Cade, Janet
Abstract: Associations between dietary factors and general cognition in the elderly have been documented; however, little is known about reaction time ability in relation to midlife diet. The present study aimed to investigate associations between reaction time and midlife dietary factors, specifically foods, nutrients and Mediterranean diet (MeDi) pattern. The UK Women's Cohort Study collected dietary information from middle-aged women (52 (sd 9·4) years old) using a validated 217-item FFQ in 1995–1998. In 2010–2011, a sub-group of 664 participants completed online reaction time ability tests including simple reaction time (SRT) and choice reaction time; 503 participants were eligible for analysis. Participants were grouped into fast and slow groups by their median reaction time. The intake of particular foods, nutrients, adherence to the MeDi and cooking methods (roasting/baking, frying and barbecuing/grilling) were explored in relation to reaction times. We did not find any significant associations between reaction times and investigated foods, nutrients or adherence to the MeDi in adjusted models. However, consumers of roasted/baked fish and fried vegetables were associated with slower SRT (adjusted OR 1·46, 95 % CI 1·00, 2·13, P = 0·049; and adjusted OR 1·64, 95 % CI 1·12, 2·39, P = 0·010, respectively) compared with non-consumers of that particularly cooked food. Overall, our findings show no significant associations between midlife diet and reaction time ability 10–15 years later.